Identification of scavenger receptor B1 as the airway microfold cell receptor for Mycobacterium tuberculosis - Haaris Khan; Vidhya R. Nair; Cody R. Ruhl; Samuel Álvarez-Arguedas; Jorge L Galvan Rendiz; Luis H. Franco; Linzhang Huang; Philip W. Shaul; Jiwoong Kim; Yang Xie; Ron B. Mitchell; Michael U. Shiloh (2020)
Mycobacterium tuberculosis (Mtb) can enter the body through multiple routes, including via specialized transcytotic cells called microfold cells (M cell). However, the mechanistic basis for M cell entry remains undefined. Here, we show that M cell transcytosis depends on the Mtb Type VII secretion machine and its major virulence factor EsxA. We identify scavenger receptor B1 (SR-B1) as an EsxA receptor on airway M cells. SR-B1 is required for Mtb binding to and translocation across M cells in mouse and human tissue. Together, our data demonstrate a previously undescribed role for Mtb EsxA in mucosal invasion and identify SR-B1 as the airway M cell receptor for Mtb.